Honoring two stalwarts of photosynthesis research: Eva-Mari Aro and Govindjee - Jajoo, Anjana; Subramanyam, Rajagopal; Garab, Győző; Allakhverdiev, Suleyman I (Photosynthesis research, 2023)
On behalf of the entire photosynthesis community, it is an honor, for us, to write about two very eminent scientists who were recently recognised with a Lifetime Achievement Award from the International Society of Photosynthesis Research (ISPR) on August 5, 2022; this prestigious Award was given during the closing ceremony of the 18th International Congress on Photosynthesis Research in Dunedin, New Zealand. The awardees were: Professor Eva-Mari Aro (Finland) and Professor Emeritus Govindjee Govindjee (USA). One of the authors, Anjana Jajoo, is especially delighted to be a part of this tribute to professors Aro and Govindjee as she was lucky enough to have worked with both of them.
Keywords: Photosynthesis; Govindjee Govindjee; Achievement; odměny a ceny; ISPR awards; Eva-Mari Aro; Awards and Prizes; úspěšnost; fotosyntéza